2022
DOI: 10.3390/nu14030609
|View full text |Cite
|
Sign up to set email alerts
|

Non-Targeted Dried Blood Spot-Based Metabolomics Analysis Showed Rice Bran Supplementation Effects Multiple Metabolic Pathways during Infant Weaning and Growth in Mali

Abstract: Rice bran contains essential nutrients, antioxidants, and bioactives with anti-inflammatory and diarrheal protective properties important for infants. This 6-month randomized controlled trial investigated the effects of heat-stabilized rice bran supplementation during Malian infant weaning. Fifty healthy 6-month-old infants were randomized to a rice bran intervention (N = 25) or non-intervention control group (N = 25). Intervention infants received dose-escalating rice bran supplementation for 6 months (1–5 g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 49 publications
(55 reference statements)
0
17
0
1
Order By: Relevance
“…Nine prebiotic studies met the inclusion criteria [ [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] ], and their study characteristics are presented in Table 2 . The interventions were conducted on 1392 children.…”
Section: Resultsmentioning
confidence: 99%
“…Nine prebiotic studies met the inclusion criteria [ [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] ], and their study characteristics are presented in Table 2 . The interventions were conducted on 1392 children.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the relation between total fecal sIgA, diversity indexes, and differences in bacterial species is challenging because interaction of the microbiota with the mucosal immune system is complex, involving not only direct interactions but also metabolite cross-feeding ( 50 ). Further evaluation of metabolites between cohorts and associations with OTUs could help to explain the correlation between total fecal sIgA and specific bacteria ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Urine and DBS metabolomics was performed as previously described. [20,22] Both specimens used a Waters AC-QUITY ultra-performance liquid chromatography (UPLC) and a Thermo Scientific Q-Exactive high resolution/accurate mass spectrometer interfaced with a heated electrospray ionization (HESI-II) source and Orbitrap mass analyzer. The informatics system consisted of four major components, the Laboratory Information Management System (LIMS), the data extraction and peak-identification software, data processing tools for quality control (QC) and compound identification, and a collection of information interpretation and visualization tools for use by data analysts.…”
Section: Methodsmentioning
confidence: 99%
“…[20] Untargeted metabolomics is a sensitive tool for characterizing numerous metabolites within a biological matrix that can be utilized to identify a targeted selection of metabolites for further analysis. [21][22][23] Urine and dried blood spots (DBS) are ideal biological fluids to examine dietary exposures due to ease in collection and sensitivity to dietary metabolite abundance changes over time. [24] We recently reported on the cooked cowpea flour metabolome used in this child and pregnant women feeding study; the cowpea flour analysis demonstrated distinct metabolite profiles for cowpea flour compared to other legumes.…”
Section: Introductionmentioning
confidence: 99%